2022
DOI: 10.3390/cells11071079
|View full text |Cite
|
Sign up to set email alerts
|

Leaky Gum: The Revisited Origin of Systemic Diseases

Abstract: The oral cavity is the gateway for microorganisms into your body where they disseminate not only to the directly connected respiratory and digestive tracts but also to the many remote organs. Oral microbiota, travelling to the end of the intestine and circulating in our bodies through blood vessels, not only affect a gut microbiome profile but also lead to many systemic diseases. By gathering information accumulated from the era of focal infection theory to the age of revolution in microbiome research, we prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 146 publications
1
7
0
Order By: Relevance
“…The fetal placental unit may not be as sterile as previously thought, with nearly a third of placental specimens confirmed to contain intracellular bacteria in the substrate, the tissue layer and the underside of the maternal-fetus interface ( Pelzer et al, 2017 ; Park et al, 2022 ). Moreover, a placenta microbiome study reported that the placental microbiome is in fact more closely related to the oral microbiome than to the urogenital tract microbiome, which is what is generally expected.…”
Section: Deterioration Of Periodontal Status Correlates With Adverse ...mentioning
confidence: 93%
“…The fetal placental unit may not be as sterile as previously thought, with nearly a third of placental specimens confirmed to contain intracellular bacteria in the substrate, the tissue layer and the underside of the maternal-fetus interface ( Pelzer et al, 2017 ; Park et al, 2022 ). Moreover, a placenta microbiome study reported that the placental microbiome is in fact more closely related to the oral microbiome than to the urogenital tract microbiome, which is what is generally expected.…”
Section: Deterioration Of Periodontal Status Correlates With Adverse ...mentioning
confidence: 93%
“…Despite these associations, there are also direct mechanisms by which the oral microbiome can contribute to systemic diseases independently of oral diseases. Three main mechanisms have been proposed for how the oral microbiome is able to impact the rest of the body: (1) the translocation of oral microbes into other regions, (2) the translocation of oral microbiome metabolites, and (3) the instigation of immunological and inflammatory modulations that have systemic effects (Hajishengallis 2015;Thomas et al 2021;Kleinstein, Nelson, and Freire 2020;Park et al 2022;Bowland and Weyrich 2022). Via these mechanisms, various NCDs have been shown to be directly caused by the oral microbiome; these interactions are described in greater detail in the following sections.…”
Section: Revised Amendments From Versionmentioning
confidence: 99%
“…Three main mechanisms have been proposed for how the oral microbiome is able to impact the rest of the body: (1) the translocation of oral microbes into other regions, (2) the translocation of oral microbiome metabolites, and (3) the instigation of immunological and inflammatory modulations that have systemic effects ( Hajishengallis 2015 ; Thomas et al . 2021 ; Kleinstein, Nelson, and Freire 2020 ; Park et al . 2022 ; Bowland and Weyrich 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was accepted that bacteria are present only on the skin and mucous membranes. It is now known that through some types of tissues that have the ability to flow (phenomenon of “leaky gum” and “leaky gut”) [ 4 , 5 ] bacteria and their metabolites can enter the circulation [ 6 ], and from there – various organs and tissues and be an important component of the tissue microenvironment [ [7] , [8] , [9] , [10] ]. Some organs in mammals, for example, the mammary gland, have unique, not yet fully studied mechanisms of bacterial transport from the intestine [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%